Isolation and Characterization of Protease Producing Strain Bacillus Cereus from Odorous Farm Soil in Tropical Area - Fitriyanto, Nanung Agus (2014)
industries as dehiring and bating agent of animal hides and skins. These enzymes known as an ecofriendly alternative agent to minimize a chemical used in unhairing and dehiring processes. The objective of this research is to isolate microbes from soil around odorous farm area at Yogyakarta which has protease activity and strain TD5B, TD5K dan LS2B were succesfully obtained and confirmed to produce extracellular protease. The 16S rRNA gene sequence analysis of both three strains demonstrated that these isolates showing high similarity to species of Bacillus cereus NC740T (AP007209). The G+C content of total DNA for strain TD5B, TD5K dan LS2B is 53.4 mol%, 53.6 mol% and 53.5 mol% respectivelly. The addition of 1-2% casein in agar medium significantly increase the colony size and clear zone can be confirmed for all strains as an evidence the ability of isolates in producing extracellular protease. Growing in 1/10 liquid meat extract medium, top of exponential phase can be reached at 16 hours from starting point of cultivation. Enzyme produced by isolates have potential as dehiring and bating agent since the enzyme activity at pH 11 and temperature 60°C succesfully confirmed of both three strains.